Luxury limbo: temporal techniques of border control and the humanitarianisation of waiting. (2018) - McNevin, Anne; Missbach, Antje
In this article, we examine temporal techniques of border control including prolonged periods of waiting, stasis and indeterminacy that increasingly characterise the experience of refugees, asylum seekers and other irregular migrants. We argue that these temporal techniques are enhanced and legitimised by parallel efforts to improve accommodation for irregular migrants - a process we call the humanitarianisation of waiting. We focus on the Indonesian context, where growing numbers of refugees wait for resettlement elsewhere, whilst housed in non-custodial alternatives to detention. We show how the promotion of alternatives to detention as humane and pragmatic enables containment strategies pursued through migration management to persist under a cloak of benevolence. The result is a kind of 'luxury' limbo that refugees experience and through which it becomes harder to disentangle the managerial emphasis on migrant care from the more pernicious practices of border security. The paper's analytical distinction between spatial and temporal techniques of border control illuminates the vexed politics of humanitarianism with respect to human mobility in the Indonesian context and beyond.